Flying on their own wings: young and adult cuckoos respond similarly to long-distance displacement during migration - Thorup, Kasper (Sci Rep, 2020)
Common cuckoos Cuculus canorus are obligate nest parasites yet young birds reach their distant, species-specific wintering grounds without being able to rely on guidance from experienced conspecifics – in fact they never meet their parents. Naïve marine animals use an inherited navigational map during migration but in inexperienced terrestrial animal migrants unequivocal evidence of navigation is lacking. We present satellite tracking data on common cuckoos experimentally displaced 1,800 km eastward from Rybachy to Kazan. After displacement, both young and adult travelled similarly towards the route of non-displaced control birds. The tracking data demonstrate the potential for young common cuckoos to return to the species-specific migration route after displacement, a response so far reported exclusively in experienced birds. Our results indicate that an inherited map allows first-time migrating cuckoos to locate suitable wintering grounds. This is in contrast to previous studies of solitary terrestrial bird migrants but similar to that reported from the marine environment.